PEMBERDAYAAN MASYARAKAT MELALUI KEGIATAN KULIAH KERJA NYATA (KKN) MAHASISWA UNIVERSITAS BENGKULU PERIODE 86 TAHUN 2018 DI DESA TEBAT MONOK KABUPATEN KEPAHIANG - Diah Gustina; Ilham Adbullah; Sofino Sofino (UNIB Press, Universitas Bengkulu, 2019)
This study aims to describe: (1) The formulation of the contents of the program of the University of Bengkulu Student Working Period 86 period in Tebat Monok Village 2018 Academic Year; (2) The form of community empowerment carried out as a realization of the 86th period of the University of Bengkulu Student Work Lecture program in Tebat Monok Village 2018 Academic Year; (3) Results of community empowerment carried out through the 86th period of the Bengkulu University Student Work Lecture in Tebat Monok Village 2018 Academic Year; (4) Role of Supervising Lecturers (DPL) in assisting the activities of the 86 Year University of Bengkulu University Real Work Period 2018 in Tebat Monok Village. This study used a qualitative approach to the research subjects of Students of the University of Bengkulu in the 86 86 2018 period in Tebat Monok Village the government of Tebat Monok village as a Lapanga Advisor, and University of Bengkulu P3KKN. Data collection is done by interviewing techniques and documentation. The technique used in data analysis is data reduction, data presentation, and conclusion drawing. Triangulation is used to explain the validity of the data by using source triangulation, technique triangulation, and time triangulation. The results of the study show: (1) The process of formulating the program content is done by drafting the KKN student work program through the KKN workshop. (2) The form of implementation of community empowerment carried out is training in packaging techniques and product labeling. (3) The results of community empowerment are carried out, namely the fulfillment of the basic needs of the community of Tebat Monok Village in the field of Entrepreneurship. (4) The role of Field Advisors is to carry out their duties and functions in accordance with existing provisions, namely by holding orientation until giving objective values. Keywords: Community Empowerment, Training, Family Welfare.